2019
DOI: 10.3367/ufne.2018.01.038281
|View full text |Cite
|
Sign up to set email alerts
|

Strong isospin symmetry breaking in light scalar meson production

Abstract: Siberian Branch of the Russian Academy of Sciences, prosp. Akademika Koptyuga 4, 630090 Novosibirsk, Russian FederationIsospin symmetry breaking is discussed as a tool for studying the nature and production mechanisms of light scalar mesons. We are concerned with isospin breaking effects with an amplitude ∼ √ m d − mu (instead of the usual ∼ m d − mu), where mu and m d are the u and d quark masses, whose magnitude and phase vary with energy in a resonance-like way characteristic of the KK threshold region. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 214 publications
(529 reference statements)
0
7
0
Order By: Relevance
“…(14) and (15) [taking into account Eq. (16)] coincide with the ππ scattering phase δ 0 0 ðsÞ below the K þ K − threshold where η 0 0 ðsÞ ¼ 1.…”
Section: R ¼mentioning
confidence: 80%
See 2 more Smart Citations
“…(14) and (15) [taking into account Eq. (16)] coincide with the ππ scattering phase δ 0 0 ðsÞ below the K þ K − threshold where η 0 0 ðsÞ ¼ 1.…”
Section: R ¼mentioning
confidence: 80%
“…Reviews of the current situation can be found, for example, in Refs. [3,4,15,16]. At the same time, the further expansion of the area of the q 2q2 model validity for light scalars on ever new processes seems to us extremely interesting and important.…”
Section: Qq-probe In Operationmentioning
confidence: 97%
See 1 more Smart Citation
“…An anomalously large production of the π 0 f 0 (980) decay mode of η(1405/1475), which is forbidden by isospin symmetry, was reported by the BESIII Collaboration [5], and that large amount production and the narrow f 0 (980) lineshape in the ππ distribution, which is the order of the mass difference of the charged and neutral kaons due to the isospin symmetry breaking, are explained well by the triangle mechanism [6][7][8][9] (see also Ref. [10] for a review article). The triangle diagram considered in the work is composed of K * KK and its charge conjugation shown in Fig.…”
Section: Introductionmentioning
confidence: 82%
“…In [68] the f 1 (1285) decays into a 0 (980)π 0 , f 0 (980)π 0 and isospin breaking were studied. An interesting proposal was also discussed in [69,70]: to study the anomalous isospin breaking decay f 1 (1285) → π + π − π 0 in central exclusive production of the f 1 . There is another important decay channel, K Kπ, with branching fraction 9% [44] which can be used for f 1 meson studies in CEP.…”
Section: Discussionmentioning
confidence: 99%